Implementation of Efficient Liquid Solar Array System Using GSM and Launchpad - Shinde, Siddhi Sandip (International Journal of Computer Sciences and Engineering, 2019)
Power crisis problem is one of the biggest challenge in-front of country. Increasing demand of fossil fuels and its constant depletion is the major concern that shifts our focus to use renewable energy sources which are sustainable to environment and mainly unlimited source of energy. Out of the some renewable energy sources solar energy is excellent alternative to use as it is not area specific. Besides its all advantages land acquisition is the major problem associated with solar power plant installed on land which is solve by liquid solar array concept. Most of solar project of government is in hot and dry region or higher radiation region which affects the efficiency of solar panel. Due to this innovative concept to set up liquid solar array on water bodies which prevents evaporation of water and growth of algae. Automatically cleaning of panel is done which increases panel efficiency and reduces manpower effort associated with cleaning it. Additionally Fresnel lens is used to concentrate sunlight on panel and monitoring is done by GSM and controller used here is Launchpad. Launchpad is also known as Msp430.